POINT ESTIMATION OF THE PARAMETER OF GEOMETRIC DISTRIBUTION UNDER A PARTICULAR RANDOM CENSORING TEST - HE ChaoBing (Jixie qiangdu)
The MLE of geometric distribution are studied by ML method and EM algorithm under a particular random censoring test. The proof of existence and uniqueness of MLE and EM iterative formula of the parameter are given. The asymptotic variance of EM estimation is obtainde by Louis algorithm. Random simulation results show that the MLE and EM estimation are both fairly accurate,and make little difference.